Nurses' educational practices in Family Health Strategy - Darlisom Sousa Ferreira; Flavia Regina Souza Ramos; Elizabeth Teixeira (Associação Brasileira de Enfermagem, 2021)
ABSTRACT Objectives: to analyze the nurse's educational practice in Family Health Strategy. Methods: descriptive study with a qualitative approach, whose data production used the World Café group technique, in two meetings, with 26 nurses of a health district of Manaus-AM. The technique used was Categorial-Thematic Content Analysis. Results: the study generated two units of analysis: Political and Organizational Configuration of Educational Work at ESF and Operational Configuration of Educational Work at ESF, revealing the necessary (re)configurations in co-management, in the centrality of the subject for the planning of educational work, and in (re)pactuation between the management of services and training institutions to overcome contradictions in the implementation of National Policies on Permanent Education and Basic Health Care. Conclusions: the configuration of nurses' educational practice at ESF works toward interactions, organized to respond to health policies, incorporating creativity in doing, but facing numerous obstacles.